1999
DOI: 10.1021/ja991740e
|View full text |Cite
|
Sign up to set email alerts
|

Structures and Partial Stereochemical Assignments for Prymnesin-1 and Prymnesin-2:  Potent Hemolytic and Ichthyotoxic Glycosides Isolated from the Red Tide Alga Prymnesium parvum

Abstract: Two glycosidic toxins, prymnesin-1 (PRM1) and prymnesin-2 (PRM2) have been isolated from cultured cells of the red tide phytoflagellate Prymnesium parvum, and the gross structure of PRM2 C96H136Cl3NO35 has been reported in a previous contribution. The molecule possesses unique structural features:  a C90 unbranched carbon chain except for a single methyl, five contiguous ether rings (6/6/6/7/6), four distinct 1,6-dioxadecalin units, conjugated double and triple bonds, chlorine and nitrogen atoms, and an uncomm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
56
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 124 publications
(62 citation statements)
references
References 22 publications
6
56
0
Order By: Relevance
“…parvum is an invasive and harmful algal species that produces a number of toxins (Shilo 1971(Shilo , 1981. Igarashi et al (1999) identified the toxins prymnesin 1 and prymnesin 2 as two potent ichthyotoxins. However, recent work by Henrikson et al (2010) found that the primary toxins in our cultures and in Lake Texoma were galactoglycolipids, collectively called parvisides, with most toxicity in laboratory cultures due to the derivative stearidonic acid, a fatty acid component that is freed from the parvisides by esterase activity.…”
Section: Discussionmentioning
confidence: 99%
“…parvum is an invasive and harmful algal species that produces a number of toxins (Shilo 1971(Shilo , 1981. Igarashi et al (1999) identified the toxins prymnesin 1 and prymnesin 2 as two potent ichthyotoxins. However, recent work by Henrikson et al (2010) found that the primary toxins in our cultures and in Lake Texoma were galactoglycolipids, collectively called parvisides, with most toxicity in laboratory cultures due to the derivative stearidonic acid, a fatty acid component that is freed from the parvisides by esterase activity.…”
Section: Discussionmentioning
confidence: 99%
“…Brevetoxins (BTXB 2 and BTXA 7), the first members of LSPs, have been extensively studied by Nakanishi's 76 and Shimizu's groups. 77 Besides these toxins, ciguatoxin, 78-81 maitotoxin, prymnesins, 82,83 and yessotoxins (YTX 9) [84][85][86] have been found in association with fish-killing red tides or toxic seafood. More than 50 compounds belonging to LSP have been reported so far.…”
Section: Activity-relevant Conformation and Bimolecular Interactions mentioning
confidence: 99%
“…However, the toxic metabolites responsible for bloom toxicity are not established in Heterosigma akashiwo , making studies of viral impact on toxicity difficult. On the other hand, reports of toxic P. parvum metabolites are numerous and include fatty acids [48], glycerolipids [49] and very large ladder-frame polyether toxins, known collectively as the prymnesins [50,51,52]. Reports of cases of toxic and non-toxic blooms of Prymnesium and other harmful algal species [37] has led to speculation that an ecological trigger exists for toxicity.…”
Section: Discussionmentioning
confidence: 99%